Dopamine D2 receptor-mediated circuit from the central amygdala to the bed nucleus of the stria terminalis regulates impulsive behavior - Kim, Bokyeong (2019)
Impulsivity is closely associated with addictive disorders, and changes in the brain dopamine system have been proposed to affect impulse control in reward-related behaviors. However, the central neural pathways through which the dopamine system controls impulsive behavior are still unclear. We found that the absence of the D2 dopamine receptor (D2R) increased impulsive behavior in mice, whereas restoration of D2R expression specifically in the central amygdala (CeA) of D2R knockout mice (Drd2−/−) normalized their enhanced impulsivity. Inhibitory synaptic output from D2R-expressing neurons in the CeA underlies modulation of impulsive behavior because optogenetic activation of D2R-positive inhibitory neurons that project from the CeA to the bed nucleus of the stria terminalis (BNST) attenuate such behavior. Our identification of the key contribution of D2R-expressing neurons in the CeA → BNST circuit to the control of impulsive behavior reveals a pathway that could serve as a target for approaches to the management of neuropsychiatric disorders associated with impulsivity.